Atorvastatin Induced Erythrocytes Membrane Blebbing. Issue 3 (9th August 2019) - Rana, Rumaisa Bashir; Jilani, Kashif; Shahid, Muhammad; Riaz, Muhammad; Ranjha, Mazhar Hussain; Bibi, Ismat; Asghar, Asma; Irfan, Muhammad
Atorvastatin, an inhibitor of 3-hydroxy-3-methylglutaryl-coenzymeA reductase, is usually used for the treatment of hypercholesterolemia. Besides its pharmacological and side actions, its toxic effects on human nucleus devoid of erythrocytes are still unknown. Eryptosis is an alternative term used for suicidal erythrocyte death. Membrane blebbing is among the common markers of eryptosis. In this study, eryptotic effect of atorvastatin was investigated by exposing the erythrocytes for 48 hours to different concentrations (1-10 µM) of atorvastatin. The experimental work related to investigation of eryptosis was done by cell size measurement and calcium channel inhibition. As a possible mechanism of eryptosis, atorvastatin-induced oxidative stress was evaluated by determining catalase, glutathione peroxidase, and superoxide dismutase activities. Similarly, necrotic effect of atorvastatin was also determined by hemolytic assay. Results of our study illustrated that the tested doses of atorvastatin may induce oxidative stress as observed by significant reduction in superoxide dismutase, glutathione peroxidase, and catalase activities as well as induce eryptosis, featured by erythrocytes membrane blebbing. The study concluded that induction of oxidative stress by atorvastatin may lead to eryptosis.